Investigating the growth of carbon traces in cardboard in oil-paper insulation - Zhang, Zhanlong; Pan, Xiaomei; Dong, Zijian; Zhong, Jiarong; Wang, Xuemeng (Frontiers in Energy Research, 2023)
A large amount of contaminants are collected on the cardboard surface of the valve-side bushing outlet of a converter transformer that has been operating for a long period, and can cause the performance of the oil–paper insulation to degrade. The analysis of their energy spectrum has shown that these contaminants contain free carbon. To investigate causes of the formation of these carbon traces, the authors of this study analyze their law of growth on the surface of the insulating paper in the presence of pure insulating oil and insulating oil containing carbon particles. We examined the influence of carbon tracks of different lengths on the breakdown voltage along the surface of the oil–paper insulation. The results showed that carbonization on the surface of the insulating paper generated carbon traces in pure insulating oil and eventually led to the formation of conductive channels. Moreover, carbon traces were generated by carbon particles deposited on the surface of the insulating paper in insulating oil containing carbon particles. The carbon traces grew from the high-voltage electrode to the ground electrode along the direction of the electric field in both types of oils. The formation of the conductive channel through the poles of the paper in insulating oil containing carbon particles required a lower voltage and a shorter discharge time than that in pure insulating oil. As the concentration of the carbon particles increased, the rate of growth of carbon traces on the surface of the insulating paper increased such that the oil–paper insulation failed earlier than otherwise. Long carbon traces were formed on the surface of the insulating paper in case of a high concentration of carbon particles under the DC pre-pressure mode, and this led to a reduction in the breakdown voltage along the surface of the oil–paper insulation.